Data hiding by using AES Algorithm - Prof. Dr.Rafidah Mohamad (Wasit Journal of Computer and Mathematics Science, 2022)
Data hiding is the art of hiding data for various purposes such as; to maintain private data, secure confidential data and so on. Securely exchange the data over the internet network is very important issue. So, in order to transfer the data securely to the destination, there are many approaches like cryptography and steganography. In this research we propose an AES algorithm for embedding the data into the images which is implemented through the Microsoft .NET framework using the C#.NET.